Does the intent match the output: Aligning development goals with training load in youth basketball - Lever, J. R.; Duffield, R.; Murray, A.; Bill, H. A.; Bartlett, J. D.; Fullagar, H. H. K. (European Journal of Sport Science, 2026)
This study investigated the alignment between external training load metrics and coach-prescribed development goals in an elite youth basketball setting. External training load data from training drills were collected over two years from 25 elite male youth basketball players in a full-time residential academy. At the start of each term, coaches developed and assigned individual developmental goals (IDGs) for each player. Using inductive thematic analysis, these IDGs were retrospectively grouped into four overarching development goal categories (defensive, offensive, skill, and physical) and 16 specific goal types (e.g., cutting, shooting, and load tolerance). Separately, external load metrics were recorded during all on-court training sessions using Catapult Vector S7 devices. To align IDGs with external load metrics, two multinomial logistic regression models were developed to classify (1) development goal category and (2) specific goal type (SGT) using per-minute external load metrics. Both models achieved 66% classification accuracy (Kappa = 0.60). Key predictors, such as high-intensity deceleration counts, vertical PlayerLoad, and high-speed running distances, were retained in both models following stepwise selection. Model performance was strong, with large reductions in AIC (Delta AIC = 1224.1 and 2540.7, respectively), demonstrating that coach-assigned IDGs were associated with distinct external load profiles. Additionally, accumulated training time differed significantly across specific goal types, reflecting systematic variation in emphasis across the season. These findings demonstrate that external training load metrics reflect the structure of coach-assigned development goals, offering a data-driven framework to evaluate alignment between training design and physical demands in youth basketball.